Clitics that don't climb - Gračanin Yuksek, Martina (Array, 2019)
In this article the behavior of clitics in subject- versus object-control infinitival constructions is explained by arguing that the two constructions have different structures. I argue that object-control infinitival constructions are CPs, and are therefore structurally richer than subject-control infinitival constructions, which are TPs and do not involve a CP projection. This results in different behavior of the clititcs in the two configurations.